THE USE OF MINI-DRAMA TO IMPROVE STUDENTS’ SPEAKING SKILL - Viranci, Nofila Cici; Sudarsono, Sudarsono; Luwandi, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was conducted in order to know how mini-drama improve students? speaking skill to the year-8 students at Class A of MTsN 2 Pontianak in the academic year 2018/2019. This research was conducted through Classroom Action Research (CAR) in three cycles. The subject of this research was the English teacher and 39 students of Class A in MTsN 2 Pontianak. In collecting the data, the writer used field notes, observation checklist, and speaking test as the tools of data collection. The result showed that using mini-drama improve students' speaking skill. Moreover, students and teacher's behavior improved by using mini-drama as the technique to teach speaking skill especially in asking and giving information about a person's ability. Therefore, the writer positively recommends the teacher to use a mini-drama as one of the various techniques in the teaching and learning process, especially in teaching speaking for asking and giving information about a person's capability. Keywords: Asking and Giving Information about A Person?s Capability, Mini-drama, Speaking skill